Revista “Realidade” e ditadura civil-militar: análise dos perfis de Luiz Fernando Mercadante sobre os líderes do governo ditatorial (1966-1970) - Migotto Filho, Jonas (2020)
The present study, inserted in the line of research of Memory and Patrimony of the Postgraduate Program in History of the Universidade Federal de Santa Maria, proposes an analysis of six profiles published in the “Realidade” magazine between the years 1966 and 1970: “Feliz aniversário Seu Artur”, “Êste é o Humberto”, “Um garôto chamado Artur”, “Dona Yolanda, a presidenta”, “Há um novo tempêro no poder” and “Êste é o presidente”. Written by the journalist Luiz Fernando Mercadante, the texts narrate, directly or indirectly, traces of the life of the first three leaders of Brazil's dictatorial government. Understood in this work as one of the stages of memory dispute, the press helped to build the image of dictators in the period. Based on Luiz Gonzaga Motta and John B. Thompson, a critical analysis of the narratives will be realized, in order to reveal the strategies of symbolic construction present in the texts and their ideological character as they represent the support of the power instituted by the military regime. To this purpose, the three narrators involved in the process of producing the profiles will also be analyzed: the vehicle, the journalist and the profiled character, seen here in a broader way, as the political context of each moment of the Civil-Military Dictatorship. Thus, it is also intended to understand the tension between transgression and conservation in the pages of “Realidade”.